2019
DOI: 10.1136/bjsports-2018-100461
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events of exercise therapy in randomised controlled trials: a systematic review and meta-analysis

Abstract: ObjectiveTo evaluate the relative risk (RR) of serious and non-serious adverse events in patients treated with exercise therapy compared with those in a non-exercising control group.DesignSystematic review and meta-analysis.Data sourcesPrimary studies were identified based on The Cochrane Database of Systematic Reviews investigating the effect of exercise therapy.Eligibility criteriaAt least two of the authors independently evaluated all identified reviews and primary studies. Randomised controlled trials were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
76
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 26 publications
(32 reference statements)
4
76
0
2
Order By: Relevance
“…The incidence of coach-and participant reported ex-AEs was higher in this study than previously reported in exercise trials for cancer patients [4,13]. The reason for this may be that we included all, even minor ex-AEs, and gathered the data in a systematic way [13] as well as having different definitions of ex-AEs.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…The incidence of coach-and participant reported ex-AEs was higher in this study than previously reported in exercise trials for cancer patients [4,13]. The reason for this may be that we included all, even minor ex-AEs, and gathered the data in a systematic way [13] as well as having different definitions of ex-AEs.…”
Section: Discussionmentioning
confidence: 78%
“…The incidence of coach-and participant reported ex-AEs was higher in this study than previously reported in exercise trials for cancer patients [4,13]. The reason for this may be that we included all, even minor ex-AEs, and gathered the data in a systematic way [13] as well as having different definitions of ex-AEs. For instance, other studies including women with breast cancer exercising at HI having reported no ex-AEs when participants reported ex-AEs to the coaches [32], or minor ex-AEs, such as hypotension or dizziness after maximal treadmill testing while monitored by coaches [39].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…As such the risk of severe or unexpected adverse events (AE) is low. 28 Exercise and an increase in physical activity may initially increase the risk of AEs such as pain, fatigue or muscle soreness or increased falls through increased activity. To reduce the risk of AEs the exercise programme will be tailored to the abilities of the participants.…”
Section: Phase 2: Feasibility Cohort Rctmentioning
confidence: 99%